Microtensile bond strength of radicular dentin to non-metallic posts bonded with self-adhesive cements - Roperto, Renato Cassio; El-Mowafy, Omar; De Toledo Porto-Neto, Sizenando; Marchesan, Melissa Andrea (My University, 2010)
Microtensile bond strength of radicular dentin bonded to glass fiber posts with self adhesive cements. Purpose. The purpose of this study was to evaluate the microtensile bond strength (μTBS) of glass fiber posts bonded to intraradicular dentin when self-adhesive resin cements were used. Methods. Eighty single-rooted teeth were endodontically treated and assigned to 8 groups (n=10). Two types of post were used: a glass fiber post (REFORPOST (RP)) and a flexible fiber post (EVERSTICK (EP)). These were cemented using 1 of 3 types of self-adhesive cement (UniCem (UN), BisCem (BC) or MaxCem (MC)) and a resin cement was used with a separate primer/bonding agent (Panavia F (PN)) for the control group. Specimens were thermocycled in water baths in temperatures ranging between 5°C - 55°C (3000 cycles), stored in water at 37°C for 1 week and then sectioned into 1.0 mm thick slices (3 from the cervical and 3 from the middle thirds of the roots). Slices were trimmed mesio-distally and subjected to μTBS testing. Data were analyzed by 3-way ANOVA. Post hoc Tukey intervals for comparison between the 2 post materials, 4 types of cement and 2 root regions were calculated (α=.05). Results. The multiple comparison test ranked dentin adhesion of the different resin cements in the following ascending order: MC < UN = BC < PN (P<.001). Statistical analysis also showed higher adhesion values for all cements associated with EP posts when compared to RP posts (P<.001). Some self-adhesive resin cements were capable of producing mean μTBS to radicular dentin similar to that obtained when control resin cement was used. Higher mean bond strength values in the cervical region were observed for all groups when compared to the middle third of root dentin. Clinical Significance The use of fiber-reinforced composite posts in combination with resin cements has been reported to be effective in restoring endodontically treated teeth with wide or flared canals, because fiber posts and resin composite have similar module of elasticity to teeth enabling loading forces to be transferred consistently from the restoration to the tooth structure. This study addresses one of the main concerns of such use, the bonding mechanism of different composite materials resin cements to posts and root dentin. © 2010 Nova Science Publishers, Inc.